Dynamics of democracy (Brief edition) (Brown & Benchmark, 1997)
This is a brief edition of the text Dynamics of Democracy, 2nd Edition. It aims to give students and teachers an alternative to encyclopedic textbooks without sacrificing coverage of key elements of American government and politics such as civil liberties, the constitution and federalism